Holistic Approach on Early-Onset Type 2 Diabetes Mellitus Patient with Suspected Mental Retardation and Family History of Metabolic Disease: A Case Report - I Gede Aswin Parisya Sasmana; Made Ayu Kurniati Atmaja; Lorena Samanta Adelina; Wayan Citra Wulan Sucipta Putri; Putu Aryani; Ida Ayu Diah Pramita Kurnia Dewanti; Ida Bagus Made Candra (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2026)
A 46-year-old unmarried male, Mr. IMAP, presented to a primary health center (Puskesmas) in Bangli Regency accompanied by his father due to persistent fatigue and blurred vision for the past month. The patient has a history of mental retardation since childhood, making communication difficult and necessitating constant support from his father. He was diagnosed with early-onset type 2 diabetes mellitus (T2DM) at the age of 15 and has been attending regular follow-ups at the health center. His recent random blood glucose was recorded at 560 mg/dL. He also has a history of asthma. Both of the patient’s parents have T2DM and hypertension, with extended family members on both sides also having a history of metabolic diseases. The patient is unemployed and performs only light household chores. He denies smoking, alcohol use, or substance abuse. Physical examination revealed a body mass index of 20.45 kg/m², blood pressure of 140/80 mmHg, and no significant abnormalities aside from elevated blood pressure. Home visits were conducted to holistically identified patient’s problem and provide comprehensive treatment. Upin first visit, repeated blood pressure measurements confirmed Stage I hypertension. Psychiatric evaluation indicated a flat affect, poor verbal response, minimal facial expression, and a lack of emotional awareness. The patient could only answer in one or two words and had no insight into his condition. He admitted to never brushing his teeth, and when informed about his illness, showed no reaction.Through heteroanamnesis, the father reported that the patient had a fixed daily routine, primarily consisting of sleeping, cleaning the house, and collecting firewood. The patient lacks understanding of his condition, and all aspects of his care—including insulin injections and clinic visits—are managed by his father.